2022
DOI: 10.1002/adfm.202210351
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired and Hierarchically Textile‐Structured Soft Actuators for Healthcare Wearables

Abstract: Soft pneumatic actuators possess the increasing potential for various healthcare applications, such as smart wearable devices, safe human‐robot interaction, and flexible manipulators. However, it is difficult to translate the existing technologies to commercial applications due to their inefficient volumetric power, sophisticated control with high operation pressure, slow production, and high cost. To overcome these issues, herein, a caterpillar‐inspired actuator using hierarchical textile architectures based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Mastering nature, the creatures of the natural world have taught us much. , The lotus leaf, with its “untouched by mud” feature; the shark, with its sea-swimming abilities; and the human finger, with its ultrasensitive properties, all have their unique strengths. In this work, a drag reduction and antifouling integrated piezoresistive sensor was prepared using a sandwich structure that combines three elements.…”
Section: Resultsmentioning
confidence: 99%
“…Mastering nature, the creatures of the natural world have taught us much. , The lotus leaf, with its “untouched by mud” feature; the shark, with its sea-swimming abilities; and the human finger, with its ultrasensitive properties, all have their unique strengths. In this work, a drag reduction and antifouling integrated piezoresistive sensor was prepared using a sandwich structure that combines three elements.…”
Section: Resultsmentioning
confidence: 99%
“…(g) Sewing and weaving. Reproduced from ref : Yang, M.; Wu, J.; Jiang, W.; Hu, X.; Iqbal, M. I.; Sun, F. Adv . Funct .…”
Section: Manufacturing Methodsmentioning
confidence: 99%
“…As shown in Figure 3g, Yang et al combined wool fancy yarn with a novel three-layer braided structure to construct an actuator. 45 During the spinning process, the polyurethane Roving was stretched and twisted according to the procedure and then wound on the polyester fiber with negative pressure feeding, forming a beaded structure through shrinkage, and the polyester fiber was in a free state. It is easy to integrate soft robotics into daily clothing by sewing and weaving.…”
Section: ■ Manufacturing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knitting, a long-established and ubiquitous textile manufacturing process, can easily form different looped structures by changing the stitches and raw materials online to achieve integrated sensing performance and specific mechanical properties. Kitting technology also provides an easy way to reconstruct different actuators with various deformations and functions through stitching, disassembling, and reknitting processes. In addition, the inherent flexibility, high throughput, and low-cost feature of textiles make them promising candidates for fabricating soft robotics. Previous research has demonstrated a variety of textile-based soft pneumatic actuators, but few works have been done to realize fabric-based robotics capable of proprioception and exteroception properties based on a combination of digitalized knit stitches.…”
Section: Introductionmentioning
confidence: 99%